2022
DOI: 10.3390/plants11101359
|View full text |Cite
|
Sign up to set email alerts
|

SNF1-Related Protein Kinase 1 Activity Represses the Canonical Translational Machinery

Abstract: Protein biosynthesis is achieved through translation, which consumes enormous energy. Therefore, under conditions of limited energy supply, translation progress should be strictly coordinated. Sucrose non-fermenting kinase1 (SNF1)-related protein kinase 1 (SnRK1) is an evolutionarily conserved master regulator of cellular energy stress signaling in plants. Rice (Oryza sativa) and Arabidopsis (Arabidopsis thaliana) SnRK1 enhance hypoxia tolerance and induce the expression of stress-related genes. However, wheth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Remarkably, SnRK1-mediated eIF4E and eIFiso4E phosphorylation attenuates general translation (Bruns et al, 2019). Furthermore, SnRK1 activity represses canonical protein biosynthesis without significantly changing transcript levels and protein stability (Son et al, 2022). However, under submergence conditions, SnRK1-mediated eIFiso4G1 phosphorylation confers translational enhancement of specific mRNAs, including those of core hypoxia-response genes (Cho et al, 2019).…”
Section: Translation Mechanisms Regulated By Hypoxia In Plantsmentioning
confidence: 99%
“…Remarkably, SnRK1-mediated eIF4E and eIFiso4E phosphorylation attenuates general translation (Bruns et al, 2019). Furthermore, SnRK1 activity represses canonical protein biosynthesis without significantly changing transcript levels and protein stability (Son et al, 2022). However, under submergence conditions, SnRK1-mediated eIFiso4G1 phosphorylation confers translational enhancement of specific mRNAs, including those of core hypoxia-response genes (Cho et al, 2019).…”
Section: Translation Mechanisms Regulated By Hypoxia In Plantsmentioning
confidence: 99%
“…Under such conditions, the plant must balance energy expenditure to maintain homeostasis. Work [10] showed that activation of SnRK1, a key sensor of energy stress signalling, leads to reprogramming of the transcriptome and metabolism to adapt to such cellular energy crises and survive them. SnRK1 phosphorylates the 4G1 isoform (eIFiso4G1) of the eukaryotic translation initiation factor (eIFiso17G4), which leads to a higher translational efficiency of specific transcripts, including those induced by hypoxia during flooding.…”
Section: Signaling Pathways Start Of Changesmentioning
confidence: 99%